Biofortification of crops: a sustainable tool for nutritional security in India - Yadava, Devendra Kumar; Hossain, Firoz; Choudhury, Partha Ray; Kumar, Dinesh; Singh, Anand Kumar (Indian Farming, 2018)
ICAR is committed to meet the sustainable development goals and achieve country’s slogan of ‘Kuposhan Mukt Bharat’ (Malnutrition Free India). Development of biofortified crops with enhanced micronutrients was a major focus area of ICAR. To further expedite the process of development of biofortified crops, ICAR has funded a Consortia Research Platform on ‘Biofortification in Selected Crops for Nutritional Security’, where rice, wheat, maize, pearl millet, sorghum and minor millets were targeted for nutritional enrichment. These highyielding biofortified crops besides serving as an important source for livelihood to poor people, assume great significance in nutritional security. Further Extension Division of ICAR has launched two very important projects viz., Nutrisensitive Agricultural Resources and Innovation and Value Addition and Technology Incubation Centres in Agriculture through Krishi Vigyan Kendras which will definitely help in popularization and promotion of the biofortified crop varieties and their products. KVKs are already working on Agri-Nutri Smart Village (A2N) Model which focuses on Nutri Farming System, Agri-Nutri Education, Agri-Nutri Capacity Building and SHG-Farmer Nutri Clubs.